A study on mobile applications developed for children with autism - Aziz, N.S.A. (Springer Verlag, 2019)
The emerging of mobile technology leads to the extensive used of mobile application for learning purposes of the children with autism. Autism is a neurological disorder that affects the childrenâs behavior and their ability to communicate and interact socially. A lot of studies have been conducted on using mobile application to assist the children with autism to increase their social and communication skills. Mobile applications are now widely used, not only for entertainment and social networking, but also for education. The used of mobile applications in education has extend from dictionaries to special purpose education. This paper reviews six mobile applications developed to assist the children with autism for various purposes. This review will provide a summary of initial studies and preliminary findings for future development of enhanced application. Â© Springer Nature Switzerland AG 2019.